PERANAN KEPOLISIAN TERHADAP PERBUATAN MAIN HAKIM SENDIRI YANG DILAKUKAN MASYARAKAT DALAM TINDAK PIDANA PENCURIAN - zulkarnaen zulkarnaen zulkarnaen (jurnal.unprimdn.ac.id, 2018)
Crime of vigilante is the term for actions to punish a party without going through a process that is in accordance with the law Law enforcement against the perpetrator of this crime must be carried out firmly, straightforwardly and accurately based on justice, truth value and not based on an interest. Based on this background, this study was carried out using normative and juridical empirical juridical methods. The research data were secondary data obtained through literature studies. The research data were then analyzed to facilitate interpretation and understanding of the results of the analysis to answer the existing problems. a. The ability of the offender to be responsible for his actions. b. Reason for reasons that justify the perpetrator who abolishes criminal liability for the maker. If the three elements have been fulfilled the perpetrator can be subject to criminal law. If there are no reports of abuse, and no community wants to provide witness testimony, then this action is difficult to prove the truth. This study suggests that law enforcement against vigilante crimes to punish people must be upheld. The perpetrators of this crime must be handed over to law enforcement officers to be processed according to the law so that the community that the action of the vigilante to punish people is categorized as one of the crimes.